Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/6490984
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Effect on the Ductility, Flexural Strength, and Permeability of Concrete

Abstract: Recently, remarkable types of carbon nanofilaments called carbon nanotubes (CNTs) have raised the interest of many concrete and cementitious composite researchers due to their significant mechanical, electrical, thermal, kinetic, and chemical properties. These nanofilaments are considered promising applicants to use in producing high-performance cement-based composite materials. In this research, the effect of CNT use on the flexural strength, strain capacity, permeability, and microstructure of concrete was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Presently, carbon nanotubes are also added to concrete as a nanofiller because they possess a higher surface area and unusual mechanical characteristics. Mohsen et al [94] examined the influence of carbon nanotube utilization on the microstructure, permeability, strain capacity, and flexural strength of concrete. The test results confirmed this nanomaterial increased the concrete beam ductility by approximately 150%.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…Presently, carbon nanotubes are also added to concrete as a nanofiller because they possess a higher surface area and unusual mechanical characteristics. Mohsen et al [94] examined the influence of carbon nanotube utilization on the microstructure, permeability, strain capacity, and flexural strength of concrete. The test results confirmed this nanomaterial increased the concrete beam ductility by approximately 150%.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…The agglomeration of long and large diameter CNTs might adversely affect the compressive strength. [6], [9], [12], [8], [13] Previous literatures have suggested that flexure strengths of 0.03 and 0.08 wt% batches increased by anywhere between 30-40 % with low standard deviations. However, for batches of 0.15% and 2.5% the change was above 100% with high standard deviations.…”
Section: Flexural and Compressive Strengthmentioning
confidence: 99%
“…Este comportamiento, según lo indicado por la Ref. [42] está relacionado con la mejora de las propiedades mecánicas del concreto por la adición del NTC, produciendo un compuesto más denso con mayor resistencia y capacidad de deformación.…”
Section: Resistencia a La Tracciónunclassified